2014
DOI: 10.1155/2014/416028
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Aminothiols, Nitrite, Nitrate, and Malondialdehyde in Myelodysplastic Syndromes in the Context of Clinical Outcomes and as a Consequence of Iron Overload

Abstract: The role of oxidative stress in the initiation and progression of myelodysplastic syndromes (MDS) as a consequence of iron overload remains unclear. In this study we have simultaneously quantified plasma low-molecular-weight aminothiols, malondialdehyde, nitrite, and nitrate and have studied their correlation with serum iron/ferritin levels, patient treatment (chelation therapy), and clinical outcomes. We found significantly elevated plasma levels of total, oxidized, and reduced forms of cysteine (P < 0.001) ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…Also, our study showed that the bilirubin system of HL patients seems to be affected by their oxidative status. Regarding MDS patients, Pimkova et al 23 did not observe increased MDA levels which contrasts with our findings in this group of patients. But, Goncalves et al 16 in agreement with our study observed increased ROS levels and consequently the involvement of oxidative stress to the development of MDS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, our study showed that the bilirubin system of HL patients seems to be affected by their oxidative status. Regarding MDS patients, Pimkova et al 23 did not observe increased MDA levels which contrasts with our findings in this group of patients. But, Goncalves et al 16 in agreement with our study observed increased ROS levels and consequently the involvement of oxidative stress to the development of MDS.…”
Section: Discussioncontrasting
confidence: 99%
“…Among them, myelodysplastic syndromes (MDS) represent a unique scenario as oxidative stress can increase due to both transfusion-dependent iron overload and dyserythropoiesis itself. 16 Publications from different groups have presented measurements of different oxidative stress biomarkers for different hematological malignancies such as acute lymphoblastic leukemia (ALL), Hodgkin lymphoma (HL) and Myelodysplastic syndromes [17][18][19][20][21][22][23] . Battisti et al measured plasmatic thiobarbituric acid-reactive substances (TBARS), serum protein carbonylation, whole blood catalase (CAT) and superoxide dismutase (SOD) activities in ALL patients 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Pimkova et al [ 41 ] reported that mean plasma tHcy of 14.5 μmol/L in patients with myelodysplastic syndromes was greater than that of 9.4 μmol/L in healthy controls. In these patients, mean plasma ferritin was elevated (although not significantly), whereas plasma iron was normal.…”
Section: Iron-hcy Interactionmentioning
confidence: 99%
“…Williams et al [46] in a comparative study of plasma aminothiols between healthy subjects and stroke patients observed elevated t-Hcy (9.9 § 0.6 mM/L) among stroke patients than the healthy control (6.5 § 0.3mM/L). Elevated levels of plasma t-Hcy were also reported in myelodysplastic patients compared to the healthy blood donors by Pimkova et al, [47] Pfeiffer et al [37] reported plasma t-Hcy and L-Cys concentrations for healthy males and females, respectively, in the order of 9.1 § 1.8 and 298 § 29 mM/L for males and 7.8 § 1.7 mM/L and 280 § 32 mM/L for females. Higher plasma t-Hcy values in the order of 11.69 § 2.32 mM/L for male and 9.45 § 1.78 mM/L for female were reported in healthy control subjects by Tokgoz et al [44] in their comparative study in patients having atherosclerosis, hypogonadism and Behcet's disease.…”
Section: Discussionmentioning
confidence: 66%